Spring Security 3.1. - Winch, Robert (Community experience distilled., 2012)
This practical step-by-step tutorial has plenty of example code coupled with the necessary screenshots and clear narration so that grasping content is made easier and quicker. This book is intended for Java web developers and assumes a basic understanding of creating Java web applications, XML, and the Spring Framework. You are not assumed to have any previous experience with Spring Security.